War, Coups & Terror : Pakistan's Army in Years of Turmoil - Cloughley, Brian (Rawalpindi, Pakistan Army Publishing House, 2012)
A major study on the Pakistan army discusses the Pakistan military's controversial role in government, its position as a force in the fight against al-Qaeda and the Taliban, and operations against the 2003-2004 tribal uprising.
Include Index
Keywords: Pakistan -- Pakistan. Army -- Military policy